First identification of ORF virus causing contagious ecthyma in Morocco (MOR20): Genomic, phylogenetic, and sequence variants analyses for vaccine design - Zouhair Elkarhat; Ikram Tifrouin; Zahra Bamouh; Khalid Omari Tadlaoui; Mehdi Elharrak (PLoS ONE, 2025)
The ORF virus induces a zoonotic contagious ecthyma disease, affecting small ruminants such as sheep and goats. ORF virus has not been identified in Morocco, and there is no vaccination protocol against contagious ecthyma. In this study, we analyzed the genome sequence of a new strain isolated in Morocco (MOR20) from a flock of sheep showing suspicious signs of Sheepox virus infection. ORFV MOR20 strain was isolated after 2 initial blind passages on Heart cells. The cytopathic effect was characterized by aggregation, swelling and detachment of cells, appearing 4 days after infection. The virus was harvested on day 6 pi with a titer of 107.2 TCID/ml. ORFV MOR20 was sequenced using the Illumina NovaSeq 6000 platform. After employing several bioinformatics tools, we identified that ORFV MOR20 shares 98.59% similarity with the TVL strain virus, which is used in a commercial live vaccine. Additionally, We aligned 33 ORFV genomic sequences with MOR20 sequences and visualized the pairwise comparisons using a Heat Map. ORFV was classified into two genetic groups: those isolated from sheep and those from goats. This was confirmed by a phylogenetic tree. Furthermore, we analyzed genetic variants identified in the MOR20 strain in comparison with ORFV TVL strain and found 636 sequence variants. Some genes, such as ORFV086, ORFV112, and ORFV132, have a particularly high number of sequence variants. All in all, ORFV MOR20 isolate represents a promising candidate for further studies aimed at developing a standardized vaccine against contagious ecthyma.